ANALISA PETROFISIKA UNTUK KARAKTERISASI RESERVOAR DAN ESTIMASI VOLUMETRIK HIDROKARBON DI TEMPAT PADA RESERVOAR GE, LAPANGAN âXâ - , GARDA ERLANGGA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Research about petrophysical analysis for reservoir characterization and hydrocarbon volumetric estimation had been done. The data that is used as research object including 24 wells data of GE reservoir, âXâ field, offshore north west java basin. This research propose to determining the petrophysical properties of reservoir and use it for reservoir characterization and estimating hydrocarbon volumetric in place. The research starts from quality control of the data like pre-calculation, environmental correction, badhole identification, log normalization, and continued to petrophysical analysis through deterministic analysis. As the properties are calculated, it is used for reservoir characterization based on the distribution of petrophysical properties and hydrocarbon volumetric estimation in place. From the analysis, the petrophysical properties of GE reservoir are obtained such as shale volume, effective porosity, water saturation, and permeability with shale volumeâs average is 29%, effective porosityâs average is 18%, water saturationâs average is 64%, and permeabilityâs average is 18%. For reservoir characterization and hydrocarbon volumetric estimation in place, interpretation was done by divided the reservoir into five different blocks in counter clockwise direction due to a fault existence that sealing the blocks. The distribution of effective porosity and permeability show a smaller trend as the direction to south west, which the reservoirâs blocks those have good potential as a hydrocarbon reservoir based on estimation of hydrocarbon volumetric in place are block 1, 5, 3, 2, 4, meanwhile total of volumetric hydrocarbon estimation in place are 9.100.000 barrel oil and 900.000.000 cubic feet gas.